Guide Wire-Assisted Urethral Dilation in Pediatric Urology: Experience of a Single Guide Wire-Assisted Urethral Dilation in Pediatric Urology: Experience of a Single Surgeon - Chiang, David T; Dewan, Paddy A; Dewan, Paddy A (Urology Journal, 2009)
<!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE AR-SA MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--> <!-- /* Font Definitions */ @font-face {font-family:"Cambria Math"; panose-1:2 4 5 3 5 4 6 3 2 4; mso-font-charset:1; mso-generic-font-family:roman; mso-font-format:other; mso-font-pitch:variable; mso-font-signature:0 0 0 0 0 0;} @font-face {font-family:Tahoma; panose-1:2 11 6 4 3 5 4 4 2 4; mso-font-charset:0; mso-generic-font-family:swiss; mso-font-pitch:variable; mso-font-signature:1627400839 -2147483648 8 0 66047 0;} /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal {mso-style-unhide:no; mso-style-qformat:yes; mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Times New Roman","serif"; mso-fareast-font-family:"Times New Roman";} p.a, li.a, div.a {mso-style-name:??; mso-style-unhide:no; mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; text-align:justify; line-height:150%; mso-pagination:none; font-size:12.0pt; mso-bidi-font-size:10.0pt; font-family:"Times New Roman","serif"; mso-fareast-font-family:"Times New Roman";} p.CharCharCharChar, li.CharCharCharChar, div.CharCharCharChar {mso-style-name:" Char Char Char Char"; mso-style-unhide:no; margin-top:0cm; margin-right:0cm; margin-bottom:8.0pt; margin-left:0cm; line-height:12.0pt; mso-line-height-rule:exactly; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Tahoma","sans-serif"; mso-fareast-font-family:"Times New Roman"; mso-bidi-font-family:"Times New Roman";} .MsoChpDefault {mso-style-type:export-only; mso-default-props:yes; font-size:10.0pt; mso-ansi-font-size:10.0pt; mso-bidi-font-size:10.0pt;} @page Section1 {size:612.0pt 792.0pt; margin:72.0pt 72.0pt 72.0pt 72.0pt; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0;} div.Section1 {page:Section1;} --> <!--[if gte mso 10]> <![endif]--> Introduction: A simple technique to dilate urethral stricture using guide wire and sheath dilator has been described in pediatric urology. The aim of this study was to report the long-term outcome of the children who underwent dilation of the urethral stricture using guide wire and sheath dilator. Materials and Methods: From 1999 to 2004, a total of 52 children with documented urethral stricture were managed by urethral dilation using guide wire.Â  Data on the cause of urethral stricture, operation, postoperative recovery, follow-up cystoscopic appearance, and patientâ€™s outcome were audited and analyzed.Â Â  Results: The mean age of the patients was 5.6 Â± 2.3 years (range, 2 to 18 years). The mean period of the follow-up was 4.5 Â± 2.4 years (range, 3.8 to 6.5 years). Twenty-two patients (42.3%) did not require any further surgical treatments. However, urethral stricture in 13 patients (25.0%) progressed significantly, and therefore, they needed further surgical interventions. The complications included minor urinary tract infections in 3 and bladder spasm in 2 patients. No case of false passage or sepsis was encountered. Conclusion: Guide wire-assisted urethral dilation avoids the risks associated with blind dilation techniques and continues to be a safe alternative for urethral strictures in selected cases. However, in our experience, less than half of the patients became â€œrecurrence freeâ€ after two dilation attempts. We recommend that urethral dilation be considered only in selected cases and emergency settings.Â Â Â Â Â 